The Role of RPA (Robotic Process Automation) In Digital Transformation: Qualitative Research to Show a Perspective of 5 Years of Experience - Andrzej SOBCZAK (Communications of International Proceedings, 2025)
This paper examines five years of enterprise-level experience with robotic process automation (RPA) to determine its actual contribution to digital transformation, and to generate actionable guidance for management practice. Although early RPA scholarship predicted radical labour displacement, rigorous longitudinal evidence on mature, large-scale deployments - and their interaction with digital transformation programmes - remains scarce, particularly in CEE subsidiaries of multinationals. This study addresses this empirical gap by providing practice-based insights from organisations that have deployed ≥100 software robots for at least five years. A two-stage qualitative design was employed: (1) pilot validation of an interview protocol, and (2) fifteen semi-structured expert interviews with senior automation executives selected using purposive criteria.The organisational role of RPA is evolving along a three-stage maturity continuum - from tactical FTE reduction, to process quality optimisation, to strategic business model transformation. Mature adopters report RPA-driven acceleration of digital transformation timelines (≈30-40%), but macroeconomic volatility has re-emphasised cost containment as a key metric. Success factors include transparent multi-level communication, workforce upskilling, balanced KPI (employee and customer experience alongside efficiency), process standardisation and business-led governance. The study refines the theoretical understanding of RPA as an integral, socio-technical accelerator of digital transformation and provides managers with an evidence-based blueprint for scaling automation without undermining organisational resilience.
Keywords: Robotic Process Automation; RPA; digital transformation; Qualitative research